The Influence of Total Quality Management (TQM) on Quality Cost Efficiency and Managerial Performance and the Implications for Company Performance - Elvina, Elvina; Anggraeni, Silvia; Sasongko, Sonnya Nurman; Erlandian, Amanda Yunne (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The study aimed to determine the effect of Total Quality Management (TQM) on quality cost efficiency and managerial performance and its implications on company performance. In the research, the researchers involved 100 companies in Indonesia. The analysis used is a structural approach to the Equation Model (SEM) assisted by the Smart PLS application. The results showed that there was a significant positive effect between total quality management, quality cost efficiency, managerial performance, and total management quality on company performance mediated by managerial performance. The amount of the r square of the company’s performance variable is explained by the total quality management, quality cost efficiency, and managerial performance of 88.9%.